2016
DOI: 10.1016/j.ecss.2016.02.008
|View full text |Cite
|
Sign up to set email alerts
|

The role of pioneers as indicators of biogeographic range expansion caused by global change in southern African coastal waters

Abstract: The South African coastline is just over 3000 km in length yet it covers three major biogeographic regions, namely subtropical, warm temperate and cool temperate. In this review we examine published information to assess the possible role of climate change in driving distributional changes of a wide variety of organisms around the subcontinent. In particular we focus on harmful algal blooms, seaweeds, eelgrass, mangroves, salt marsh plants, foraminiferans, stromatolites, corals, squid, zooplankton, zoobenthos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(18 citation statements)
references
References 136 publications
(155 reference statements)
3
15
0
Order By: Relevance
“…The southeastern coast of Australia, including NSW, has been identified as a global warming hot-spot, a region experiencing greater increases in temperature than the global average (Hobday & Lough, 2011). To our knowledge, this study is the first recorded range extension of any euryhaline invertebrate in this climate change hot-spot, and one of the few examples globally of a range extension by any euryhaline invertebrate in a climate change hot-spot (also see Whitfield et al, 2016). We do not regard our results as artefacts of limited past sampling as considerable field sampling has been conducted along the NSW coast since the 1950s by the Australian Museum and others (e.g.…”
Section: Discussionmentioning
confidence: 75%
“…The southeastern coast of Australia, including NSW, has been identified as a global warming hot-spot, a region experiencing greater increases in temperature than the global average (Hobday & Lough, 2011). To our knowledge, this study is the first recorded range extension of any euryhaline invertebrate in this climate change hot-spot, and one of the few examples globally of a range extension by any euryhaline invertebrate in a climate change hot-spot (also see Whitfield et al, 2016). We do not regard our results as artefacts of limited past sampling as considerable field sampling has been conducted along the NSW coast since the 1950s by the Australian Museum and others (e.g.…”
Section: Discussionmentioning
confidence: 75%
“…5,20 The southernmost distribution of M. morphina was previously recorded as Maputo Bay and Inhaca Island (25°57'S).The new records from St Lucia (28°13'S) and Mlalazi (28°57'S) have now substantially extended this distribution southwards.…”
Section: Resultsmentioning
confidence: 86%
“…5 The population then declined and was not detected in the lake, most likely because of a severe drought that caused widespread desiccation and hypersalinity in the region from 2005 until 2011. 5 The system then experienced increased freshwater input, resulting in lower salinities from 2011 until 2014, during which time live M. morphina reappeared and their population gradually increased. In 2015, M. morphina became overwhelmingly abundant in St Lucia.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, CCA analysis of zoobenthos in Jinan City in the spring and chemical factors through Monte Carlo screening of differences with p < .05 as the threshold of significance yielded potassium ion levels as a chemical water quality factor with a very significant difference ( p = .0042). Pekcan‐Hekim et al (), Untiedt and MacKay (), and Whitfield et al () found that Na + , potassium ions, and reducing substances in water have important effects on the distribution of zoobenthos. The primary sensitive species of zoobenthos was Limnodrilus hoffmeisteri.…”
Section: Resultsmentioning
confidence: 99%